Economic convergence and polarisation: towards a multi-dimensional approach - Benedek, József; Moldovan, Aura (Hungarian Geographical Bulletin, 2015)
The current increase of regional inequalities in Europe, and in particular in Central and Eastern Europe (CEE) has led to the reconsideration and revival of the concepts of "polarisation" and "convergence" in academic fields like regional economics, economic geography and spatial planning as well. In contrast to the classical view on these concepts determined by functionalism and topology, the new theoretical and empirical perspectives are emphasising a multidimensional perspective. In addition, there is an important debate about the relation between economic inequalities and growth. This article provides a critical overview and assessment of the theoretical and empirical work on regional inequalities with special emphasis on theories of economic and social polarisation, regional economic growth, convergence, and social inequalities. We attempt to combine two powerful concepts of polarisation and convergence, emphasising their relational and multi-scalar nature. Building on this basis, we propose a multidimensional concept of socio-economic polarisation, which comprises processes of convergence and divergence, growth and mobility in economic and social dimensions.